Design and Development of a Therapeutic Device for Drop Hand Patienst - Setyawan, Rahmatul Yoga; Purnamaningsih, Retno Wigajatri (Universitas Indonesia, 2024)
Drop hand is a condition where a person's wrist or fingers experience difficulty and weakness in performing extension and flexion movements. This paper reports the design and development of a therapeutic device for individuals with drop hand, capable of performing passive training movements, electrical stimulation, and monitoring muscle strength. The device consists of a servo motor (MG995) for passive training movements, an IC NE555 specifically used for stimulation, and a Myoware muscle sensor to monitor muscle strength in the hands of individuals with drop hand. The device is also equipped with a NodeMCU ESP8266 microcontroller that can connect to a WiFi network, allowing muscle sensor readings to be stored in Google Sheets. Initial tests showed that the device could lift weights up to 1 kg, generate electrical stimulation frequencies ranging from 2.75 Hz to 18.2 Hz, and that muscle strength monitoring could be performed in real time.